Contraceptive Sabotage - Plunkett, Leah A. (Columbia Journal of Gender and Law, 2014)
This Article responds to the alarm recently sounded by the American College of Obstetricians and Gynecologists over “birth control sabotage”—the “active interference [by one partner] with [the other] partner’s contraceptive methods in an attempt to promote pregnancy.” Currently, sabotage is not a crime, and existing categories of criminal offenses fail to capture the essence of the injury it does to victims. This Article argues that sabotage should be a separate crime—but only when perpetrated against those partners who can and do get pregnant as a result of having sabotaged sex. Using the principle of self-possession—understood as a person’s basic right to self-ownership—this Article argues that women have a self-possessory interest in maintaining their reproductive capacity in its non-pregnant state during and after having sex to the extent they seek to establish with the use or planned use of contraception. Sabotage by sexual partners—typically male—violates this interest and merits criminal punishment. This Article proposes statutory language to criminalize sabotage that should be added to the revision of the Model Penal Code currently underway. Not only would this addition likely survive any Equal Protection challenge, it would arguably serve to strengthen the existing constitutional right to non-procreative sex by setting meaningful limits on one partner’s ability to interfere unilaterally with the other partner’s contraceptive decisions.